Crux: um arcabouço de software para desenvolvimento de aplicações web - Thiago da Rosa de Bustamante (2008)
To produce quality software, in a cost effective manner, is necessary a systematic reuse of software models, designs and implementations previously tested. Among all reuse methods, we can emphasize the application frameworks. Combining design and code reuse, they represent the state of the art in terms of reuse in object oriented softwares.We present Crux, an application framework created to help the development of applications on the Web domain. These applications are complex distributed systems that are arising fast in number and importance. For many companies they are a key factor for success in business.The Crux framework aims to help rich interfaces creation, improving quality of interaction for users and simplifying the development for programmers.